Narrative of Dyslexic Children: Methodological Issues - Balčiūnienė, Ingrida; Kornev, Aleksandr N. N. (Respectus Philologicus, 2015)
The paper presents the methodology of narrative elicitation of dyslexic children. The experimentwas conducted in Saint Petersburg (Russia) testing 9–10 year old children. The experimental group consisted of 12 children with dyslexia, and a control group contained 12 peers without any developmental disorders. Each of the subjects performed two tasks: storytelling according to a picture sequence and retelling another picture sequence. The narrative elicitation procedure was controlled from the perspective of story complexity, task order and story mode. The descriptive statistical analysis evaluated the impact of particular types of narrative elicitation on a quality of narrative in the experimental and control groups. A statistically significant difference of the impact of task order, narrative mode, and story complexity on the narrative of dyslexic children encourages to study the methodology of narrative analysis even more comprehensively and be especially careful in selecting visual stimuli for populations with atypical language development.